RELASI MEDIA MASSA DAN DAKWAH KONTEMPORER - Ihdal Minan (al-Balagh : Jurnal Dakwah dan Komunikasi, 2016)
Mass media have an important role in today religious life of society. The relationship between religion and mass media is mutual relationship with many influential factors involved. The article explains this relationship from various view points and approaches. The facts found show that beside giving positive support, mass media also brings negative effects in the process of religious spreading. The pragmatism of media causes the media have not orientated on the growing of constructive values anymore, but have tended to be manipulative.